Land Reallotment over the Course of the Development of a Rural Settlement in Ukraine - Malashevskyi, Mykola; Kovalchuk, Ivan; Malashevska, Olena (Geomatics and Environmental Engineering, 2021)
The study is dedicated to land reallotment in the course of land use alteration in Ukraine. The case of the development of an individual residential block in an agricultural area is considered. The issue of the alteration of the spatial characteristics of land plots and changes in their designated use have been highlighted. The objective of the article is the substantiation of land reallotment at the level of an individual residential block on agricultural land which is privately owned by a number of landowners. The preconditions for the development of land reallotment in a rural‑type settlement in the suburban area of a big city have been substantiated. Alternative approaches to land reallotment have been suggested. A comparative analysis of the suggested approaches and their practical approbation have been carried out. The change of land plot spatial characteristics in the course of reallotment by means of various reallotment scenarios has been analysed. Land plot value after reallotment in each scenario has been specified. The practicability of each approach depending on the initial conditions has been substantiated. The research can be used in the course of rural settlement development planning, the coordination of measures on land use type alteration with landowners and land users, with private landowners or the implementation of local community initiatives.